2012
DOI: 10.1155/2012/874509
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Al-Doped TiO2Visible-Light Photocatalyst for Low-Concentration Mercury Removal

Abstract: High-quality Al-doped TiO2visible-light photocatalyst was prepared via a single-step direct combination of vaporized Ti, Al, and O2using a 6 kW thermal plasma system. Results showed that the formed Al-doped TiO2nanoparticles were a mixture of anatase and rutile phase and had a size between 10 and 105 nm. The absorption spectra of the nanoparticles shifted towards the visible light regions, depending on the Al2O3addition. Ti4+and Ti3+coexisted in the synthesized Al-doped TiO2; the Ti3+concentration, however, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…Al doping effects were studied by many researchers [102][103][104][105][106]. Shirley et al studied electronic and optical properties of Al-doped anatase and rutile TiO 2 from ab initio calculations [107].…”
Section: Transition Metal Doping Effects On the Bandgap Of Tiomentioning
confidence: 99%
“…Al doping effects were studied by many researchers [102][103][104][105][106]. Shirley et al studied electronic and optical properties of Al-doped anatase and rutile TiO 2 from ab initio calculations [107].…”
Section: Transition Metal Doping Effects On the Bandgap Of Tiomentioning
confidence: 99%
“…In addition, Yuan et al 1193 2012d and 2012e investigated the effect of UV intensity on Hg 0 removal using TiO 2 -aluminum silicate fiber with 1194 UV irradiation, and the results indicated that UV irradiation was critical to the successful oxidation of Hg 0 , and 1195with the decrease of UV intensity, photocatalytic oxidation efficiency for Hg 0 evidently reduced due to the 1196 reduction of photoexcited active species. In addition, Hsi(2012) andTsai (2011Tsai ( , 2012 synthesized oxygen-vacant , mechanism and kinetics of Hg 0 removal using TiO 2 photocatalytic AOTs 1201 3.7.1 Products of Hg 0 removal using TiO 2 photocatalytic AOTs 1202The products of Hg 0 removal using TiO 2 photocatalytic oxidation are important information for the recovery 1203 of mercury resources and avoiding new secondary mercury contamination Wu et al 1998. determined the reaction 1204 products of Hg 0 removal by in situ-generated TiO 2 with UV irradiation using the combination of XRD and 1205 electron dispersive X-ray spectroscopy (EDS).…”
mentioning
confidence: 99%
“…1(c)) of the Al-doped TNPWs contains TNPs and TNWs phases with some additional peaks. The additional peaks at 35.151, 43.351, 52.501 and 57.501 are indexed to the Al phase [29]. When the Al-doped level is 20%, the sample has an obvious characteristic peak (1 1 À 1) at 35.151, which confirms the formation of Al phase with monoclinic crystal structure [30].…”
Section: Xrd Tem and Sem Analysismentioning
confidence: 99%